Gene Modification of Mesenchymal Stem Cells and Articular Chondrocytes to Enhance Chondrogenesis. (19th May 2014) - Gurusinghe, Saliya; Strappe, Padraig
Abstract : Current cell based treatment for articular cartilage and osteochondral defects are hampered by issues such as cellular dedifferentiation and hypertrophy of the resident or transplanted cells. The reduced expression of chondrogenic signalling molecules and transcription factors is a major contributing factor to changes in cell phenotype. Gene modification of chondrocytes may be one approach to redirect cells to their primary phenotype and recent advances in nonviral and viral gene delivery technologies have enabled the expression of these lost factors at high efficiency and specificity to regain chondrocyte function. This review focuses on the various candidate genes that encode signalling molecules and transcription factors that are specific for the enhancement of the chondrogenic phenotype and also how epigenetic regulators of chondrogenesis in the form of microRNA may also play an important role.